Controle biológico de Dalbulus maidis (Delong & Wolcott, 1923) (Hemiptera: Cicadellidae) com Beauveria bassiana (Balsamo) Vuillemin E Metarhizium anisopliae (Metschn) Sorokin - Cecchin, Christian Alverar (My University, 2022)
Corn occupies the second position among the main Brazilian agricultural commodities. However, the productivity of this crop can be affected by insect-pests, which, if not handled properly, can cause losses. Because of this, the control must be done effectively. Biological control has been gaining prominence as a practice with low impact on the environment. The objective of this work was to evaluate the efficiency of the entomopathogenic fungus Beauveria bassiana (Bovemip) isolated IBCB 66 (88.0 x 109 UFC/g) at a dose of 1 kg/ha, and Metarhizium anisopliae (Metamip) isolated IBCB 425 (4.5 x 1010 conidia/g of product), at a dose of 22.2 g/ha, both from the Promip company, on individuals of D. maidis. The negative control was distilled water and the positive control was the chemical insecticide Connect® (imidacloprid + beta-cyfluthrin) at a dose of 750 mL/ha. The experimental design used was entirely randomized blocks, using five replicates for each treatment, with each replicate consisting of five individuals, totaling 25 individuals per treatment. The data were submitted to variance analysis and the means were compared to each other using Tukey's test at 5% probability. According to the evaluations at 7 and 14 days after application, it was observed that the biological products did not differ statistically from the negative control, but indicated another form of control for D. maidis. [resumo fornecido pelo autor]
O milho ocupa a segunda posição entre as principais commodities agrícolas brasileiras. No entanto, a produtividade desta cultura pode ser afetada por insetos-praga, que se não manejados de forma adequada, podem causar prejuízos. Em função disso, o controle deve ser realizado de forma efetiva. O controle biológico vem se destacando por ser uma prática de baixo impacto sobre o meio ambiente. O objetivo deste trabalho foi avaliar a eficiência dos fungos entomopatogênicos Beauveria bassiana (Bovemip) isolado IBCB 66 (8,0 x 109 UFC/g) na dose de 1 kg/ha, e Metarhizium anisopliae (Metamip) isolado IBCB 425 (4,5 x 1010 conídios/g de produto), na dose de 22,2 g/ha, ambos provenientes da empresa Promip, sobre indivíduos de D. maidis. Como controle negativo utilizou-se água destilada e para o controle positivo utilizou-se o inseticida químico Connect® (imidacloprido + beta-ciflutrina) na dose de 750 mL/ha. O delineamento experimental usado foi em blocos inteiramente casualizados, utilizando-se cinco repetições para cada tratamento, sendo que cada repetição era composta por cinco indivíduos, totalizando 25 indivíduos por tratamento. Os dados foram submetidos à análise de variância e as médias comparadas entre si pelo teste de Tukey a 5 % de probabilidade. Conforme as avaliações em 7 e 14 dias após a aplicação, observou-se que os produtos biológicos não diferiram estatisticamente do controle negativo, porém apontaram outra forma de controle da D.maidis. [resumo fornecido pelo autor]
Keywords: Milho - Controle biológico; Pragas agrícolas - Controle biológico; Fungos entomopatogênicos; Milho - Doenças e pragas